Karakteristik Dan Fenomena Kumpulan Puisi Akun Instagram Sajak Liar Tahun 2016 - Aryana, Putri Sri (Humanis; Vol 26 No 3 (2022), 2022)
Globalization is an era that brings a lot of influence to various aspects of Indonesian people's lives. The development of technology and the use of the internet indirectly also have a big influence on the culture of a nation, including literature. In line with technological developments, writing literary works began to spread to cyberspace or the internet. This can be seen from the emergence of cyber literature on social media. The transfer of media from writing or paper to digital which is easier to access becomes one of the reasons cyber literature is more desirable as a representative media for expression. The object of cyber literature used in this research is poetry. The one of the reasons that underlies the selection of poetry as the object of research is the type of cyber literature that is most commonly found is poetry. At its appearance, cyber literature also appeared in the form of poetry. The poetry used in this study was 100 poetry samples of 2016 Sajak Liar Instagram which were selected through random sampling method. Sajak Liar is the name of a forum for expressing cyber literature in the form of social mediabased poetry in Indonesia. This study analyzes the development, characteristics and poetry phenomena of the poetry of Sajak Liar instagram account in 2016. The stylistic analysis in this study used Warren and Wellek's theory. Furthermore, research on the characteristics of cyber literature uses Nasrullah's theory of cyber communication.